Ameliorant Application on Variation of Carbon Stock and Ash Content on Peatland South Kalimantan - Siti Nurzakiah; Fahmuddin Agus; Haris Syahbuddin (JOURNAL OF TROPICAL SOILS, 2013)
Carbon stock on peatlands are large and will be easily emitted if the land is opened or drained, therefore the measurements of  carbon stocks and ash content are important to know the amount of emissions and agricultural sustainability in peatlands. This study aimed to determine carbon stock and ash content on peatlands in the Indonesia Climate Change Trust Fund (ICCTF) located in South Kalimantan on the geographic position S. 03°25’52" and E. 114°47’6.5". The experiment consisted of six treatments of ameliorant materials namely; mineral soil, peat fertilizer A, peat fertilizer T, manure, ash, and control.  The results showed that the variation of peat soil properties was very high at this location. Peat thickness ranged from 36-338 cm, and this led to high variations in carbon stocks ranged between 161.8 – 1142.2 Mg ha-1. Besides ash contents of the soil were also highly varied ranged from 3.4 – 28.5%. This natural variation greatly affected the ICCTF study design. Mineral soil treatment had a mean carbon stock (961.3 ± 61.5 Mg ha-1) which was higher and different from other treatments. High ash content was obtained in the ash treatment (18.6 ± 2.5%) and manure (15.7 ± 3.6%).  It is recommended that the analysis of plant responses and greenhouse gas emissions using a single regression analysis and multiple regression with ash content as one of the independent variables are needed.Keywords: Ash content, carbon stock, peatland,  peat thickness[How to Cite: Nurzakiah S, F Agus, and H Syahbuddin. 2013. Ameliorant Application on Variation of Carbon Stock and Ash Content on Peatland South Kalimantan J Trop Soils, 18 (1) : 11-16. doi: 10.5400/jts.2013.18.1.11][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.11]